Increase of electrodeposited catalyst stability via plasma grown vertically oriented graphene nanoparticle movement restriction. Issue 67 (7th August 2017) - Vanrenterghem, Bart; Hodnik, Nejc; Bele, Marjan; Šala, Martin; Amelinckx, Giovanni; Neukermans, Sander; Zaplotnik, Rok; Primc, Gregor; Mozetič, Miran; Breugelmans, Tom
Abstract : This work describes a general approach to prevent coalescence/agglomeration of metallic nanoparticles for the reductive cleavage of organic halides (RX). Abstract : Beside activity, electrocatalyst stability is gaining in importance. The most common degradation mechanism is the loss of the active surface area due to nanoparticle growth via coalescence/agglomeration. We propose a particle confinement strategy via vertically oriented graphene deposition to overcome degradation of the nanoparticles.